2016
DOI: 10.1515/euco-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

When Urban Planning Doctrine Meets Low Density Countryside

Abstract: Abstract:Drawing on an empirical analysis of Finnish local policy-makers' views on land use planning aims in rural areas, this paper investigates local responses to the new national planning regulations set out by the Government. According to the new norms, a dense settlement structure should be promoted not only in urban centres but also in rural areas in order to curb climate change and improve the viability of communities. Based on the data obtained from an internet-based survey conducted by a regional news… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In the process of ecological civilization construction, villages and towns are the main construction subjects of ecological civilization [2]. In the development process of rural human settlement environment construction, not only the horizontal development of human settlement environment but also the vertical development of rural human settlement environment should be considered [3]. However, the current rural construction, especially the housing construction, has many problems and often does not meet the ecological requirements.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of ecological civilization construction, villages and towns are the main construction subjects of ecological civilization [2]. In the development process of rural human settlement environment construction, not only the horizontal development of human settlement environment but also the vertical development of rural human settlement environment should be considered [3]. However, the current rural construction, especially the housing construction, has many problems and often does not meet the ecological requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Compact cities and densely built city centres are regarded as climate friendly. Accordingly, climate concern has become established as the explicit rationale for densifying regional city dynamics (Newman & Kenworthy 1989;Kenworthy 2006;Dodman 2009;Haarstad 2016;Sireni 2016; caused by urban compression have shown that the actual footprints do not necessarily follow the initial thesis. Climate strain seems to grow when populations are concentrated due to changes in consumption patterns.…”
Section: Introductionmentioning
confidence: 99%